TINJAUAN EKONOMI ISLAM TERHADAP PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) DALAM UPAYA PENINGKATAN KESEJAHTERAAN MASYARAKAT - M.Shahrul Zidane; Sopian Hakim; M.Fajar Shodeq; Renaldi Al Buchori; Maya Panorama (Journal of Innovative and Creativity (Joecy), 2026)
Corporate Social Responsibility (CSR) has evolved into a strategic instrument in modern business practice. Nevertheless, its implementation is often considered to lack substantive values, particularly within the framework of Islamic economics. This article aims to examine CSR programs from an Islamic economic perspective and analyze their contribution to improving community welfare. The method employed is a literature study through the analysis and synthesis of various relevant scholarly sources, including journal articles, research reports, and related academic documents. The findings indicate that Islam regards CSR not merely as philanthropic activity, but as a moral obligation grounded in the principles of amanah (trustworthiness), justice, and maslahah (public benefit). The concept of Islamic Corporate Social Responsibility (ICSR) integrates Sharia values into business practice, directing corporate orientation beyond profit generation toward the creation of community welfare and environmental sustainability. The maqashid al-shariah framework — encompassing the preservation of religion, life, intellect, lineage, and wealth — serves as a normative foundation for evaluating the effectiveness of CSR programs. Nonetheless, the implementation of ICSR in practice continues to face significant challenges, including insufficient reporting transparency, short-term and symbolic program design, and the inadequate internalization of Sharia values in a comprehensive manner. This study concludes that CSR oriented toward maqashid al-shariah has the potential to foster equitable and sustainable economic development, provided it is implemented consistently, participatively, and in a well-structured manner.